Prevalence, incidence and geographical distribution of Johne's disease in cattle in England and the Welsh borders - Cetinkaya, B; Erdogan, HM; Morgan, KL (British Veterinary Assoc, 1998)
The prevalence, incidence and geographical distribution of clinical Johne's disease in dairy cattle in England and the border regions of Wales mere determined by a postal survey of 3772 dairy farmers. The study area was divided into three regions; south, central and north. The response rate was 78.3 per cent. The proportion of farms that reported 'ever' having the disease was 17.4 per cent. For the 10 Sears between 1985 and 1994 it was 4.9 per cent, and only 1.5 and 1.3 per cent in 1993 and 1994 respectively. The highest prevalence figures were always in the south. The incidence rate of clinical disease was 3.0/10,000 cow-years in both years in all herds and 16.7 and 22.8/1000 cow-years in infected herds in 1993 and 1994 respectively, An estimate of the criterion validity of diagnosis by farmers was obtained by comparing the reporting of the clinical signs with positive veterinary or veterinary investigation centre diagnoses. The proportion of farmers reporting one or other of the correct clinical signs was 95.3 per cent, and 70.6 per cent reported both correct signs (diarrhoea and weightless).
Keywords: South-West England; Para-Tuberculosis; Crohns-Disease; Dairy-Cattle; Paratuberculosis; Mycobacteria